Drinking Water from Dug Wells in Rural Ghana — Salmonella Contamination, Environmental Factors, and Genotypes - Denise Myriam Dekker (International Journal of Environmental Research and Public Health, 2015)
Salmonellosis is an important but neglected disease in sub-Saharan Africa. Food or fecal-oral associated transmissions are the primary cause of infections, while the role of waterborne transmission is unclear. Samples were collected from different dug wells in a rural area of Ghana and analyzed for contamination with bacteria, and with Salmonella in particular. In addition, temporal dynamics and riks factors for contamination were investigated in 16 wells. For all Salmonella isolates antibiotic susceptibility testing was performed, serovars were determined and strains from the same well with the same serovar were genotyped. The frequency of well water contamination with Gram-negative rod-shaped bacteria was 99.2% (n = 395). Out of 398 samples, 26 (6.5%) tested positive for Salmonella spp. The serovar distribution was diverse including strains not commonly isolated from clinical samples. Resistance to locally applied antibiotics or resistance to fluoroquinolones was not seen in the Salmonella isolates. The risk of Salmonella contamination was lower in wells surrounded by a frame and higher during the rainy season. The study confirms the overall poor microbiological quality of well water in a resource-poor area of Ghana. Well contamination with Salmonella poses a potential threat of infection, thus highlighting the important role of drinking water safety in infectious disease control.